Therapeutic Decision Making in Acute Stroke due to Carotid Artery Dissection: A Potential Role for Percutaneous Vascular Intervention following Intravenous Thrombolysis - J. B. Lewis; Á. Merwick; R. Ó. Laoide; A. O'Hare; C. McGuigan (Case Reports in Vascular Medicine)
Internal carotid artery dissection (ICAD) is an important cause of acute ischemic stroke in younger patients. Potential acute treatments include anticoagulation, intravenous thrombolysis (IVT), and endovascular thrombectomy (ET). We report a case where the use of IVT followed by ET resulted in a good clinical outcome in a patient with tandem internal carotid and middle cerebral artery occlusion following ICAD.